Bis-Indoles in Medicinal Chemistry: Synthetic Advances, Biological Activities and Emerging Pharmaceutical Applications - Jadhav, Shubham; Kapupara, Pankaj; Vekariya, Hitesh (Asian Journal of Chemistry, 2026)
Bis-indole derivatives represent an important class of indole-based compounds with substantial structural diversity and broad pharmacological potential. The presence of two indole units, connected through direct bonds or diverse linkers, provides opportunities to modulate molecular conformation, target interactions and biological activity through systematic structural modification. This review provides a critical overview of recent advances in bis-indole chemistry, with emphasis on synthetic methodologies, biological activities, structure-activity relationships and emerging therapeutic applications. Conventional synthetic approaches, such as acid-catalyzed condensation, oxidative coupling and stepwise functionalization, are discussed together with more recent developments in transition-metal catalysis, multicomponent reactions, microwave-assisted synthesis, photoredox and electrochemical transformations and sustainable catalytic systems. These approaches have expanded the accessible structural diversity of bis-indoles and improved reaction efficiency, selectivity and, in several cases, sustainability. Biologically, bis-indole derivatives have been investigated across diverse therapeutic areas, including cancer, infectious diseases, inflammation, neurological and metabolic disorders. Reported mechanisms include modulation of protein kinases, topoisomerases, microtubule dynamics, inflammatory signalling, oxidative stress and drug-efflux pathways, although the strength of mechanistic evidence varies among individual compounds. Beyond conventional pharmacological applications, bis-indole frameworks have also been explored in photodynamic therapy, molecular imaging, drug-resistance modulation and drug-delivery systems. Despite extensive research, most bis-indole candidates remain at the preclinical or experimental stage. Poor aqueous solubility, limited bioavailability, metabolic instability, off-target interactions and potential toxicity remain significant barriers to clinical development. In addition, regioselective and stereoselective synthesis, scalability and reproducibility require further improvement. Future progress will depend on establishing clearer relationships among molecular structure, target engagement, biological activity, pharmacokinetic behaviour and toxicity. Integration of sustainable synthesis, medicinal chemistry, structural biology, computational modelling and data-driven approaches, supported by standardized biological evaluation, may facilitate the identification of better-characterized candidates. Such efforts could help translate the broad chemical and biological potential of bis-indoles into therapeutically relevant applications.